Partisipasi Petani Terhadap Ketersediaan Sumberdaya Air Irigasi Aceh Besar - Ainal Mardhiah; Ola Indira Sari; Teuku Fadhla; Sari Wardani; Nurhayati Nurhayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The participation of farmers who own irrigated paddy fields has an effect on the availability of water resources because the participation of farmers in managing irrigation water resources can help the availability of water in paddy fields even though the availability of water is limited. One of the factors causing the non-optimal distribution of water and the long distance between the water source and the irrigated paddy fields causes an uneven distribution of water in the paddy fields so that some farmers use water pumps to irrigate the paddy fields. The purpose of this study was to determine the level of participation of paddy farmers. irrigation on the availability of water resources in Blang Bintang District, Aceh Besar District. The data analysis model used is Likert scale analysis. The results showed that the average level of participation of irrigated rice farmers on the availability of water resources was in the medium category or 63.82%. This shows that involvement in each activity is only when entering the rice planting season. Based on the partial test (t test) shows that the variables of land area (X1), income (X2), motivation (X3) and experience (X4) partially have no significant effect on the participation of irrigated rice farmers in the availability of water resources in Blang Bintang District, Aceh BesarRegency